The Influence of Using Social Media on the Development of Small and Medium Enterprises (UKM) "Mie Ujang Gebang" - Teguh Kurniawan; Wiwin Riza Kurnia; Hasminanda Yuniasari; Rudi Sliworo Putro; M. Prima Kharisma Jabara; Kiki Rohmana; Nurul Qomariah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This study aims to determine the influence of the implementation or use of social media on the development of micro, small and medium enterprises (MSMEs). The influence of social media on increasing the marketing of Mie Ujang SMEs, and the influence of social media on increasing the productivity of Mie Ujang SMEs. This study used a direct interview method with the owner of the Ujang Noodle production located in Gebang Village, Patrang District, Jember Regency, East Java Province. Interviews were conducted in a structured manner, in-depth interviews and observations at the Mie Ujang company related to business start-up, promotion and production before social media was used, and increasing production of Ujang noodles when using social media as a promotional medium. The subjects in this research were owners and managers, employees of MSMEs who were selected using purpose sampling. This study concludes that the MSMEs observed have used social media in their companies. The most widely used social media are Facebook, Whatsapp Groups and Instagram.